The Diversity and Geographic Distribution of Cultivable Bacillus-Like Bacteria Across Black Soils of Northeast China - Liu, Junjie; Cui, Xiao; Liu, Zhuxiu; Guo, Zhaokui; Yu, Zhenhua; Yao, Qin; Sui, Yueyu; Jin, Jian; Liu, Xiaobing; Wang, Guanghua (Frontiers in Microbiology, 2019)
Bacillus-like species are gram-positive bacteria that are ubiquitous in soils. Many of Bacillus-like bacteria are demonstrated as beneficial microbes widely used in industry and agriculture. However, the knowledge related to their diversity and distribution patterns in soils is still rudimentary. In this study, we developed a combined research method of using culture-dependent and high-throughput sequencing to investigate the composition and diversity of cultivable Bacillus-like bacterial communities across 26 soil samples obtained from the black soil zone in northeast China. Nearly all bacterial 16S rDNA sequences were classified into the order Bacillales. Fifteen genera were detected, with Bacillus, Paenibacillus, and Brevibacillus being the three most abundant genera. Although more than 2,000 OTUs were obtained across all samples, 33 OTUs were confirmed as the abundant species with a relative abundance over 5% in at least one sample. Pairwise analysis showed that the diversity of Bacillus-like bacterial communities were significantly and positively correlated with soil total carbon contents and soil sampling latitudes, which suggests that a latitudinal gradient diversity of Bacillus-like bacterial communities exists in the black soil zone. The principal coordinates analysis revealed that the Bacillus-like bacterial communities were remarkably affected by soil sampling latitudes and soil total carbon content. In general, this study demonstrated that a distinct biogeographic distribution pattern of cultivable Bacillus-like bacterial communities existed in the black soil zone, which emphasizes that the strategy of local isolation and application of beneficial Bacillus-like strains is rather important in black soil agriculture development.